Origin of Voids at the SiO2/SiO2 and SiCN/SiCN Bonding Interface Using Positron Annihilation Spectroscopy and Electron Spin Resonance. (2nd March 2023) - Nagano, F.; Inoue, F.; Phommahaxay, A.; Peng, L.; Chancerel, F.; Naser, H.; Beyer, G.; Uedono, A.; Beyne, E.; De. Gendt, S.; Iacovo, S.
Abstract : To obtain reliable 3D stacking, a void-free bonding interface should be obtained during wafer-to-wafer direct bonding. Historically, SiO2 is the most studied dielectric layer for direct bonding applications, and it is reported to form voids at the interface. Recently, SiCN has raised as a new candidate for bonding layer. Further understanding of the mechanism behind void formation at the interface would allow to avoid bonding voids on different dielectrics. In this study, the void formation at the bonding interface was studied for a wafer pair of SiO2 and SiCN deposited by plasma enhanced chemical vapor deposition (PECVD). The presence of voids for SiO2 was confirmed after the post-bond anneal (PBA) at 350 °C by Scanning Acoustic Microscopy. Alternatively, SiCN deposited by PECVD has demonstrated a void-free interface after post bond annealing. To better understand the mechanism of void formation at the SiO2 bonding interface, we used Positron Annihilation Spectroscopy (PAS) to inspect the atomic-level open spaces and Electron Spin Resonance (ESR) to evaluate the dangling bond formation by N2 plasma activation. By correlating these results with previous results, a model for void formation mechanism at the SiO2 and the absence of for SiCN bonding interface is proposed.